Just transition: A conceptual review. (December 2021) - Wang, Xinxin; Lo, Kevin
Abstract: The growing attention paid to the idea of a just transition away from the incumbent fossil fuel energy paradigm has led scholars to devise diverse definitions, understandings, and viewpoints of the term. This review seeks to clarify the different perspectives surrounding the concept, to consolidate knowledge, and to provide a concise account of current debates in the literature as well as a research agenda. It identifies five themes around which the concept has been discussed: (1) just transition as a labor-oriented concept, (2) just transition as an integrated framework for justice, (3) just transition as a theory of socio-technical transition, (4) just transition as a governance strategy, and (5) just transition as public perception. Overall, this review suggests that the literature on just transition employs rich theoretical and empirical insights from various disciplines yet contains several gaps. Specifically, it argues that the literature would benefit from more empirical studies rooted in practice, more discussion on the relationship between different concepts of just transition, an expansion of geographical scope to include developing countries and non-democratic regimes, and more attention to power dynamics in just transition.